Polycythemia vera. Physical separation of normal and neoplastic committed granulocyte-macrophage progenitors. - Singer, J W (1980)
In previous studies of two patients with polycythemia vera (PV) who were heterozygous at the X-linked locus for glucose-6-phosphate dehydrogenase (G6PD), only A type enzyme was found in nonlymphoid blood cells. However, some erythroid and granulocytic colonies grown in vitro were type B and therefore arose from presumably normal progenitors. One patient had enough type B colonies (8%) that studies of the physical characteristics of normal and PV clonal colony-forming cells could be undertaken. When marrow cells were separated by velocity sedimentation at unit gravity, most PV clonal granulocyte-macrophage progenitors (CFU-C) (type A G6PD) sedimented between 6.4 and 7.2 mm/h, whereas most residual normal, type B CFU-C sedimented less than or equal to 5.9 mm/h (P = 0.04)., When blood cells were separated over a discontinuous buoyant density gradient, PV clonal CFU-C equilibrated at densities < 1.065 g/ml, whereas residual normal CFU-C were found greater than or equal to 1.065 g/ml (P < 0.01). PV clonal and residual normal erythroid burst-forming progenitors were not separable by either method. Thus PV clonal CFU-C are larger and less dense cells than are residual normal CFU-C.